Vertical coordination with growers in the supermarket fresh fruit and vegetables supply chain in Croatia - Linde Goẗz; Mario Njavro; Jon H. Hanf; Agata Pieniadz (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2009)
This paper provides further evidence on vertical coordination as a means of overcoming supply disruptions and improving product quality. In contrast to previous studies, our findings suggest that the leading model of vertical coordination between fruit and vegetables growers and supermarkets in Croatia is restricted to loose, one-year contracts which mainly specify the terms of payment without providing farm assistance. Wholesalers more often provide farm assistance to fruit and vegetables growers. We expect that the wholesalers will drop out of the fresh fruit and vegetables (FFV) supermarket supply chain since supermarkets aim to streamline the procurement system by in-creasing local procurement directly from the farmers. Thus, the amount of farm assistance provided will further decrease. Therefore, for the rather small Croatian growers to integrate in the FFV supermarket supply chain, it is even more important that they organize to meet the supermarkets' minimum quantity requirements and obtain access to a distribution facility.
Keywords: 330; Lebensmitteleinzelhandel; Wertschöpfung; Obst; Gemüse; Kleinbauern; Vertikale Integration; Kroatien